Carabelli Trait in Australian Twins: Reliability and Validity of Different Scoring Systems - Yuh Hasegawa; James Rogers; Graham Scriven; Grant Townsend (Dental Anthropology Association, 2010)
We assessed the intra- and inter-observer reliability of two methods of scoring or categorizing Carabelli trait in both primary and permanent dentitions (Hanihara, 1961; Dahlberg, 1963). By using dental casts obtained from twins, we also compared the expression of Carabelli trait within and between monozygotic (MZ) co-twins to clarify the ontogenetic processes leading to different forms of trait expression. While intra-observer concordance rates were generally good (70 - 90%), inter-observer concordance rates were poor (35 - 60%). This indicates that considerable caution is needed when comparing data for Carabelli trait derived from different samples by different researchers. By comparing categories or scores for Carabelli trait in both dentitions of MZ co-twins, we found inter-relationships between groove and cuspal forms of the feature. Although the Arizona State University system developed by Turner is commonly used nowadays to score the Carabelli trait, we would encourage researchers interested in clarifying genetic influences and ontogenetic processes in both dentitions to refer to the often over-looked plaque of Hanihara and also Dahlberg's plaque P12B. This should improve the reliability and validity of data obtained by helping to clarify the inter-relationships between the different phenotypic expressions of Carabelli trait.